The MTT: A More Comprehensive Vision Screening Test for British Columbia Schools - Reynolds, J (Canadian Journal of Optometry, 2021)
Literature regarding the vision care needs of school children indicates that visual anomalies occur in sufficient numbers to warrant recommendation of a comprehensive school vision screening program. This study investigated the referral effectiveness (accuracy) of the Keystone Telebinocular (KTT), the Modified Telebinocular (MTT) and the Snellen against a standard optometric exam.